2022
DOI: 10.3390/ani12040451
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Porcine Circovirus Type 2 Circulating in Wild Boars of Portugal during the 2018–2020 Hunting Seasons Suggests the Emergence of Genotype 2d

Abstract: Porcine circovirus type 2 (PCV-2) is associated with several syndromes affecting swine, also known as porcine-circovirus-associated diseases, of which post-weaning multi-systemic wasting syndrome stands out due to its high economic impact on swine production. Recent data suggest the increasing circulation of the PCV-2d genotype in several countries worldwide. To provide updated data on PCV-2 genotypes currently circulating in swine in Portugal, we screened wild boar stools collected from several districts acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…PCV2a was the predominant prevalent genotype before 2003, which has been gradually replaced by PCV2b from 2003 to 2010. Due to the high prevalence of PCV2 and the widely applied PCV2 vaccines since 2010, PCV2d is an emerging genotype prevalent in China 30,31 . Moreover, the coprevalence of multiple PCV2 genotypes was often observed in the same region, even in the same pig farm 2,19,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…PCV2a was the predominant prevalent genotype before 2003, which has been gradually replaced by PCV2b from 2003 to 2010. Due to the high prevalence of PCV2 and the widely applied PCV2 vaccines since 2010, PCV2d is an emerging genotype prevalent in China 30,31 . Moreover, the coprevalence of multiple PCV2 genotypes was often observed in the same region, even in the same pig farm 2,19,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to domestic pigs, PCVs have also been found to be prevalent in free-ranging wild boars in many foreign countries, including Italy ( Amoroso et al., 2021 ; Dei Giudici et al., 2020 ), Korea ( Song et al., 2020 ), Brazil ( Souza et al., 2021 ), Austria ( Auer et al., 2022 ), Ukraine ( Rudova et al., 2022 ), Hungary ( Cságola et al., 2006 ), Portugal ( de Sousa Moreira et al., 2022 ) and Germany ( Prinz et al., 2019 ), while the epizootiology of PCVs in Chinese free-ranging wild boars remains little research because of the difficulty of sample collection, although PCV2 infection was observed in hybrid wild boars from north-east China and PCVs in wild boar from Jiangxi Province of China ( Guo et al., 2019 ; Wu et al., 2022 ). Since wild boars are considered an important reservoir of animal and zoonotic pathogens, it is important to identify the epizootiology trends of important and emerging infectious diseases in wild boars for both livestock production and public health issues ( Meng et al., 2009 ; Li et al., 2019 ; Gong et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was primarily a small, spherical virus particle and deemed non-pathogenic to pigs [5]. Contrary to PCV1, PCV2 is a circulating pathogen that causes porcine circovirus-associated disease (PCVAD), including postweaning multisystemic wasting syndrome (PMWS), porcine dermatitis and nephropathy syndrome (PDNS), reproductive disorders and respiratory disease [6][7][8][9]. In 2015, a novel porcine circovirus was identified in mummified fetuses and sows and then categorized as a new circovirus species, namely PCV3 [10].…”
Section: Introductionmentioning
confidence: 99%